Physico-chemical stability of mixed orange nectar with pineapple - Souza, Leandro Alves de; Cavalcante Júnior, Natal Borges; Hunaldo, Virlane Kelly Lima; Santos, Leticia Nunes dos; Santos, Leonardo Hunaldo dos; Costa, José de Ribamar Macedo (Brazilian Journal of Production Engineering, 2024)
With the search for healthy foods, there is an increase in the consumption of fresh fruit around the world, which includes pulps, juices and nectars derived from this type of food. Drinks have been developed to improve aspects such as aroma, flavor and nutritional values, with mixed fruit drinks being another option for consumers and a trend in the international market. The objective of this work was to develop and evaluate the physicochemical stability of mixed orange and pineapple nectar. The nectar was prepared using the hot fill process and packaged in 500 mL glass and plastic containers. They were subsequently subjected to physical-chemical analyzes for vitamin C (ascorbic acid), total soluble solids, pH and total titratable acidity. It was observed that the stability of vitamin C does not depend on the type of packaging, whether glass or plastic, used for storage. However, inadequate storage temperature and time are factors that contributed negatively to maintaining the initial concentration levels of ascorbic acid in the samples.